Current concepts in the prevention of pathogen transmission via blood/plasma-derived products for bleeding disorders. Issue 1 (January 2016) - Di Minno, Giovanni; Perno, Carlo Federico; Tiede, Andreas; Navarro, David; Canaro, Mariana; Güertler, Lutz; Ironside, James W.
Abstract: The pathogen safety of blood/plasma-derived products has historically been a subject of significant concern to the medical community. Measures such as donor selection and blood screening have contributed to increase the safety of these products, but pathogen transmission does still occur. Reasons for this include lack of sensitivity/specificity of current screening methods, lack of reliable screening tests for some pathogens (e.g. prions) and the fact that many potentially harmful infectious agents are not routinely screened for. Methods for the purification/inactivation of blood/plasma-derived products have been developed in order to further reduce the residual risk, but low concentrations of pathogens do not necessarily imply a low level of risk for the patient and so the overall challenge of minimising risk remains. This review aims to discuss the variable level of pathogenic risk and describes the current screening methods used to prevent/detect the presence of pathogens in blood/plasma-derived products.